Authentic leadership, trust, and employees’ work engagement: a comparative study of Islamic and conventional banks in Malaysia - Forbis, Ahamed; Hassan, Arif; Hashim, Junaidah (2012)
The paper reports the findings of a study conducted in two types of banks in Malaysia, that is, Islamic and conventional and intended to examine differences in employees’ perception of the authenticity in managers’ leadership style, interpersonal and institutional trust and work engagement. It was expected that the faith based culture of Islamic banks will provide a strong organizational impetus to promote greater authenticity in managerial style, facilitate interpersonal and institutional trust, and together these factors should contribute to employees’ work engagement. Sample consisted of 189 employees from Islamic banks and 206 from conventional banks. Results were in the expected direction. Compared to managers of conventional banks managers from Islamic banks were rated as more authentic; hence employees had higher level of interpersonal and institutional trust, and were more engaged in their work. Results are discussed using situational strength construct.